Morphological Diversity and Selection Characters of Arracacha (Arracacia xanthorriza Bancr.) Germplasm in Colombia - GARNICA MONTAÑA, JOHANNA PAOLA; RODRIGUEZ RODRIGUEZ, OSCAR JAIR; JARAMILLO BARRIOS, CAMILO IGNACIO; CABRERA, FRANCO ALIRIO VALLEJO (Universidad Pedagógica y Tecnológica de Colombia, 2020)
Arracacha has become an important part of social nutrition in the Andean region of South America with great cultural roots. However, the only regional variety cultivated in more than 90% of the country is called yellow common, a material planted for more than 30 years that has diminished its productive potential, leaving producers with no other alternatives. 94.6% of arracacha accessions preserved in the Colombian “Sistema de Bancos de Germoplasma de la Nación para la Alimentación y la Agricultura (SBGNAA)” was mainly collected in Colombian territory. Identification, evaluation and characterization of the preserved genetic resources allow identifying the selection variables desired for future breeding programs. 96 accessions were morphologically characterized during 2016; an important genetic diversity was seen using 11 quantitative and 30 qualitative traits. Using factorial analysis for mixed data (FAMD) and cluster analysis, six completely different groups were determined according to the plant vigor, which was influenced by plant height, plant diameter, petiole length and leaf length and width. Most important qualitative traits corresponded to flesh root color, leaf secondary pigmentation, petiole secondary color and flowering ability, being the most important selection factors. Flesh root color became a selection character due to in different communities of the Colombian Andean region roots color is an important element to differentiate plant materials.